Legal Regulation of Municipal Solid Waste Treatment in the Transition of Developing Countries to ‘Green Economy’ - BEKEZHANOV, Dauren; YERKINBAYEVA, Lazzat (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
This article is devoted to legal regulation of environment protection against municipal solid waste pollution. It provides research on legal regulation of municipal solid waste treatment in Kazakhstan and foreign countries; environmental authorities’ efficiency and their cooperation in this field; safety of the population living in close proximity to places of municipal solid waste storage and disposal; legal regulation of municipal solid waste for transition toward ‘green economy’. The methodological basis of the study is legal and dialectical methods, scientific methods of research. The relevance of the research is that it represents the first comprehensive comparative study of legal regulation of environment protection against municipal solid waste pollution. Solid waste increased accumulation indicates the changes in people lifestyle. There must be developed environmentally substantiated methods of municipal solid waste treatment under modern processing. It is stated that currently there is no specific mechanism for legal regulation of municipal solid waste treatment. This violates human and citizen rights.